Lessons Learned from the Failure of "Make in India" Industrial Reform Policy - Chang Woon Nam (CESifo Forum, 2022)
Launched in 2014, the "Make in India" initiative aims to revitalize the manufacturing sector and includes heterogeneous measures that "simultaneously" support industries at different stages of development, from labor- and capital-intensive to high-tech industries and advanced services. Among others, issues such as uncertainty in the world market discouraging export activities, poverty alleviation-oriented support for labor-intensive industries versus overall productivity gains, and the complementary role of IT services in industrial modernization and growth appear to largely determine the success of India's diversified industrial policy. After seven years of policy implementation, economic indicators show that the original goals have not been met. Moreover, course corrections and a reorientation of goals, plans, and strategies are now urgently needed.
Keywords: 330